Impacts of Low Flows on Heavy Metal concentrations in Turag River Bangladesh (Journal of Environmental Science and Natural Resources, 2018)
Water flow is a vital requirement of a river to secure ecological health status. We investigated the low flow of Turag River and its effect on the heavy metals concentration. Generally, the water of the river flowed very less from January to May. The reverse result was found from June to October. Keeping in mind this fact, eight different heavy metals were statistically analyzed. We observed that during low flow season five heavy metals surpass the standard limit for irrigation. Considering irrigation standard, the order of contamination level was: Mn > Cd > Pb > Fe > Cr > Ni > Zn > Cu in low flow season. Therefore, it is necessary to maintain moderate flow in the river system.J. Environ. Sci. & Natural Resources, 10(2): 177-182 2017